Polybrominated diphenyl ethers and organochlorine compound levels in brown trout (Salmo trutta) from Andean Patagonia, Argentina - Ondarza, Paola Mariana (2011)
Polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), DDTs and endosulfan residues were analyzed in muscle, liver, gonads, gills and stomach content of brown trout (Salmo trutta) from the Andean Patagonia. PBDEs, PCBs and DDTs levels were positively correlated with lipid content, while less hydrophobic endosulfans showed a poor correlation. Endosulfan levels were about 99.9% of total contaminant (highest levels in liver 500 103 ng g1 lipid weight), with a-/b-isomers ratio >1 in all organs. These results are in agreement to the current-use of the technical endosulfan and also suggest acute exposure to this insecticide. Conversely, DDT/DDE ratio reflects fish exposure to old DDT sources, showing a DDE predominance. Gills had the highest levels of DDTs, PCBs and PBDEs, indicating they represent the main uptake pathway for such hydrophobic compounds from water column. PCBs showed the lowest levels in all organs and the PBDEs/PCBs ratios >1 agree with worldwide trends. PBDEs levels in gonads, gills, liver and muscle exceeded 80 ng g1 (lipid weight) and were higher than other values reported in the Southern Hemisphere. BDE-47 was the predominant congener, suggesting higher bioaccumulation potential and possible brown trout metabolism of higher congeners. Since there is no point source of PBDEs in the region and residues were dominated by lower brominated congeners, atmospheric transport could be the main source of these compounds. This first report of PBDEs levels in fish from Argentina contributes to the knowledge about environmental trends of these persistent organic pollutants (POPs) in remote areas such as the Andean Patagonia.